Grammatical issues according to Al-Nawawi (676 AH) in his book Correction of Al-Tanbih (Journal of the College of Basic Education, 2024)
In this paper, we'll look at some ideas about nuclear grammar. We will present its balance in traditional Arabic grammar. Then we review some of the issues contained in the book of alert and the position of nuclear them and try to meet the opinions of grammarians old and new.Nuclear grammar, if you will, is a branch of Arabic grammar that is concerned with the study of grammar by focusing on important grammar issues and strategies for their effective use. Sometimes we see him analyzing grammatical sentences to understand their precise structures and show the relationships between words. We may glimpse some of the foundations towards it, including:The first basis : analyzing grammatical sentences and understanding their structures.The second basis : understanding the relationships of words and structures accurately and logically.If we want to strike a balance between nuclear grammar and traditional grammar, we will find that nuclear grammar focuses on the effective use of grammar rules in linguistic analysis. It focuses on syntax, and also relies on traditional grammar. As for traditional Arabic grammar, it focuses on grammar rules and classification of sentences and words. It focuses on morphological grammar and follows a more sophisticated approach. .I have chosen some of the grammatical issues presented or dealt with by nuclear in his book Lamarin: one: the large number of issues dealt with in his book may be long talk and expand in many pages are not possible to discuss them in this research paper. Second: These issues will be evidence of others in revealing what has already been mentioned in nuclear grammar. I have followed the descriptive and analytical approach in all the issues presented, hoping that the approach and issues will be adequate and useful to the reader. And from God success .